2022
DOI: 10.1002/nop2.1301
|View full text |Cite
|
Sign up to set email alerts
|

The impact of interprofessional education on students' current and desired competence in diabetes care

Abstract: Aim To explore the impact of interprofessional education (IPE) on undergraduate nursing and medical students' knowledge, competence and targeted competence in diabetes care. Design Mixed methods design. Methods A voluntary IPE course of diabetes management was organized for nursing (n = 15) and medical (n = 15) students, who performed a diabetes knowledge test and self‐evaluation of diabetes competence before and after the course and were compared with non‐participating students. The participating students' fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…These included peer-assisted learning [30,36,59], Jeffries simulation theory [55], Bandura self-efficacy theory [46], Knowles's principles for Adult Learning as guidelines [53], goal theory perspective [59], model of inter-professionality, Beck's cognitive model, and social capital theory [56]. The remaining papers did not explicitly mention the theoretical background of the IPE program [29,[31][32][33][34][35][37][38][39][40][41][42][43][44][45][47][48][49][50][51][52]54,57,58,60].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These included peer-assisted learning [30,36,59], Jeffries simulation theory [55], Bandura self-efficacy theory [46], Knowles's principles for Adult Learning as guidelines [53], goal theory perspective [59], model of inter-professionality, Beck's cognitive model, and social capital theory [56]. The remaining papers did not explicitly mention the theoretical background of the IPE program [29,[31][32][33][34][35][37][38][39][40][41][42][43][44][45][47][48][49][50][51][52]54,57,58,60].…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the content, the learners were introduced to interprofessional collaborations via exposure to examples of interprofessional care of patients with specific clinical conditions (e.g., wound, ulcers, dementia, diabetes, and breast cancer) in actual setting or in simulation scenarios [31][32][33]35,45,50,51,54,60]. Nine papers reported that the content of the IPE intervention included explicit training on the different professional roles [29,32,[34][35][36]51,54,56,57], and seven papers reported IPE interventions that included training in communication skills [30,32,35,36,40,49,57].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations